The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/cancers12102815
|View full text |Cite
|
Sign up to set email alerts
|

DUX Hunting—Clinical Features and Diagnostic Challenges Associated with DUX4-Rearranged Leukaemia

Abstract: DUX4-rearrangement (DUX4r) is a recently discovered recurrent genomic lesion reported in 4–7% of childhood B cell acute lymphoblastic leukaemia (B-ALL) cases. This subtype has favourable outcomes, especially in children and adolescents treated with intensive chemotherapy. The fusion most commonly links the hypervariable IGH gene to DUX4 a gene located within the D4Z4 macrosatellite repeat on chromosome 4, with a homologous polymorphic repeat on chromosome 10. DUX4r is cryptic to most standard diagnostic techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 73 publications
1
17
1
Order By: Relevance
“…The B-progenitor ALL subtype is characterized by deregulation of the homeobox transcription factor gene DUX4 , which is reported in 4–7% of childhood B-ALL cases [ 225 ]. It was indicated that the DUX4 rearrangement is a clonal event acquired in the early stage of leukemogenesis [ 226 ].…”
Section: Genetic Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…The B-progenitor ALL subtype is characterized by deregulation of the homeobox transcription factor gene DUX4 , which is reported in 4–7% of childhood B-ALL cases [ 225 ]. It was indicated that the DUX4 rearrangement is a clonal event acquired in the early stage of leukemogenesis [ 226 ].…”
Section: Genetic Biomarkersmentioning
confidence: 99%
“…DUX4 is present in the D4Z4 repeats of the subtelomeric region of chromosome 4q or the homologous region at 10q. However, D4Z4 repeats go through the process of insertion to the IGH locus on chromosome 14 [ 225 , 228 ]. This rearrangement leads to disruption of the highly conserved C terminus of DUX4 , which is necessary for the process of DUX4 oncogenic activation.…”
Section: Genetic Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also associated with transcriptional deregulation (usually deletion) of ERG and IKZF1 del (63% and 28%, respectively) [58,59]. DUX4 patients tend to be slightly older (median age 9.8 y in Ma-Spore) [60][61][62], with low white cell counts (median 10,000/µL) [60,63,64].…”
Section: Dux4mentioning
confidence: 99%
“…These articles cover significant themes in childhood cancer research and include biological studies on the role of MYCN in poor prognosis Wilms’ tumor [ 1 ] and the mTOR complexes in rhabdomyosarcoma [ 2 ]; studies exploring biologically based treatments in ependymoma [ 3 ] and osteosarcoma [ 4 ]; a comprehensive description of a novel orthotopic model for radiation-induced glioma which will be invaluable for preclinical testing [ 5 ]; and two comprehensive review articles on leukemias. One review describes recently identified rearrangements of DUX4 with IGH in childhood B-cell acute lymphoblastic leukemia (ALL) and the diagnostic challenges associated with identifying the rearrangement [ 6 ], and the second proposes that infant acute myeloid leukemia (AML) is a biologically and clinically distinct entity from AML in older children [ 7 ]. An additional original research article [ 8 ] emphasizes the importance of monitoring for spinal deformities in children with central nervous system (CNS) tumors and the advantages of early assessment and surgical interventions where needed.…”
mentioning
confidence: 99%